Management Of Mandibular Lateral Incisor Agenesis With Skeletal Class III Malocclusion by Space Closing Technique - Inayati, Fidiyah; Ardani, I Gusti Aju Wahju (Indonesian Journal of Dental Medicine, 2018)
Background: Patients with congenital absence of a mandibular lateral incisor are often found having difficulty in achieving adequate functional occlusion. It may affect esthetics, mastication, speech, and occlusal balance. Purpose: This paper reported an agenesis treatment of one mandibular lateral incisor case using a space closure method. Case: A twenty-three years old female patient with agenesis of tooth 42, mandibular anterior crowding, multiple diastema on mandibular anterior teeth, and skeletal class III malocclusion. Case Management: Space closure method was chosen to correct the agenesis by considering the class III skeletal malocclusion and multiple diastema condition. Conclusion: Space closure method treatment improved the patient's facial and dental esthetics, and it provided a good functional occlusion, despite the absence of a mandibular lateral incisor, which generally impairs the adequate incisal guidance.